Enhancing Lipid Extraction from Chlorella vulgaris Microalgae for Biodiesel Production: Application of Natural Deep Eutectic Solvent (NaDES) in Cell Disruption - Priharto, Neil; Nadia Yasmin Dicky (School of Life Sciences and Technology, Institut Teknologi Bandung, 2024)
Natural deep eutectic solvent (NaDES) pre-treatment offers a promising alternative strategy to enhance lipid extraction efficiency from microalgae by influencing the integrity of the cell wall, thereby improving solvent accessibility to the cytoplasm and facilitating the release of intracellular lipid content. In this study, Chlorella vulgaris biomass underwent pre-treatment with four different NaDES formulations, each based on choline chloride (ChCl) with varying molar ratios: ChCl : Glycerol (1:2), ChCl : Glycerol (1:1), ChCl : Oxalic Acid (1:2), dan ChCl : Oxalic Acid (1:1).We analyzed the impact of these NaDES pre-treatments on lipid yield and fatty acid profiles. The extracted lipids exhibited an acid value of 42.56 mg KOH/g fat and a free fatty acid content of 0.25%. Samples subjected to NaDES treatment showed significant increases in lipid extraction efficiency, with lipid yields ranging from 1.25 to 2.3 times higher than those of untreated biomass extracted using hexane (p < 0.05). The highest lipid yield was observed in samples treated with ChCl : Glycerol (1:1), achieving a total lipid yield of 19.44% (w/w), more than double that of the untreated biomass. Although minor variations in fatty acid profiles were noted due to the NaDES treatment, the dominant fatty acids in each variation remained palmitic acid (C16:0, 21-29.5%) and oleic acid (C18:1, 13-43.88%).